AW-NI-6: MINERALOCORTICOID RECEPTOR ACTIVATION LEADS TO HIGH BLOOD PRESSURE DUE TO BODY POTASSIUM AND WATER LOSS. (January 2023) - Minegishi, Shintaro; Morisawa, Norihiko; Kitada, Kento; Wild, Johannes; Keat, Yam Wan; Han, Hong Yu; Marton, Adriana; Minegishi, Kaoru; Tiing, Lim Tzy; Ishigami, Tomoaki; Tamura, Kouichi; Nishiyama, Akira; et al.
Abstract : Objective: Mineralocorticoid receptor (MR) activation is known to reduce renal Na+ elimination and increase body fluid, resulting in arterial hypertension. We have reported earlier that high salt intake, chronic renal failure and psoriasis occur blood pressure increases initiated by body water loss. Here we tested the hypothesis that DOCA treatment induces a similar adaptive water conservation response that also causes arterial hypertension. Design and method: Male C57BL/6J mice on the low-salt diet (<0.1% NaCl) were divided into four groups: tap water (control), tap water with subcutaneous 25 mg DOCA (DOCA), 1% NaCl water with DOCA (DOCA salt), 1.44% NaHCO3 water with DOCA (DOCA NaBic). We performed continuous metabolic cage studies. Na+, K+, and water were measured in mice tissue by desiccation and consecutive dry ashing. Blood pressure was measured by telemetry. We also studied body composition, glucocorticoid-receptor (GR) protein/chromatin interaction, skin blood flow perfusion and renal vascular resistance. Metabolome and key enzyme activities of energy production in kidney, skeletal muscle and in liver were compared between four groups. Results: Compared to control mice, DOCA mice showed increased urine volume, lower urine osmolality and increased blood pressure. DOCA salt developed arterial hypertension within 3 days of the experiment (P < 0.001, Fig. 1A). In DOCA salt mice, K+ and water loss occurs in the initiation phase of arterial hypertension (Fig. 1B), indicating solute and water loss from the intracellular space. Further water loss was then prevented by secondary Na+ accumulation, indicating that the initial MR-driven dehydration reverted back to normal body fluid level by means of Na+ accumulation. Additional physiological adaptation to DOCA salt-driven body water loss included increased vascular resistance (Fig. 1C) and catabolic amino acid breakdown (Fig. 1D). DOCA NaBic mice showed similar massive primary K+ loss and secondary Na+ retention, but no arterial hypertension occurred (Fig. 1A). While DOCA salt decreased skin blood flow, DOCA NaBic increased it (Fig. 1C). DOCA salt mice showed renal glutamine catabolism as well as muscle protein catabolism (Fig. 1D). This catabolic state was coupled with glucocorticoid receptor binding in skeletal muscle. Conclusions: DOCA salt leads to pronounced initial K+ and water loss with hypertension. Na+ retention occurs only secondarily and is a compensatory response that reverts initial body water loss back to normal body water levels. Additional NaBic feeding reveals that the blood pressure level in mice with MR activation is determined by changes in blood flow independent of body Na+ or water content.